Potential of CRISPR/Cas13 System in Treatment and Diagnosis of COVID-19 - Khodavirdipour, Amir; Piri, Motahareh; Jabbari, Sarvin; Khalaj-kondori, Mohammad (Global Medical Genetics, 2021)
The novel coronavirus disease 2019 (COVID-19) belongs to coronaviridae families like sarbecovirus (SARS), and causes pyrexia, pertussis, and acute respiratory distress syndrome (ARDS) in major. Started from Wuhan, China, COVID-19 now forced the World Health Organization (WHO) call it a global pandemic. These dreadful figures elevate the need for rapid action for a rapid diagnostic tool, an efficacious therapy, or vaccine for such widespread disease. In this article, we reviewed all the latest research and trials including conventional antiviral medicines that have a narrow and finite effect on COVID-19. Recently, some advances were made by a nucleotide/nucleoside analogues (NUC) inhibitor (remdesivir), ivermectin (antiparasitic drug), and convalescent plasma; the later one has more recently been approved by the Food and Drug Administration (FDA). Additionally, a clinical-grade soluble human angiotensin-converting enzyme (ACE2), named hrsACE2, was able to inhibit the infection of human blood vessel organoids, as well as the human kidney organoids, by the virus. As of now, innovative therapeutics based on the CRISPR/Cas13d might overcome the challenge of COVID-19 either as a treatment option or precise and rapid diagnostic tool due to its rapid and precise nature. In this updated comprehensive rapid review, we tried to cover all recent findings in terms of genomics, diagnosis, prevention, and treatment.
Keywords: COVID-19; CRISPR/Cas13; diagnosis; hrsACE2; vaccines; ivermectin